The age of death in Japanese patients with type 2 and type 1 diabetes: A descriptive epidemiological study. Issue 8 (19th April 2022) - Nishioka, Yuichi; Kubo, Shinichiro; Okada, Sadanori; Myojin, Tomoya; Higashino, Tsuneyuki; Imai, Kenjiro; Sugiyama, Takehiro; Noda, Tatsuya; Ishii, Hitoshi; Takahashi, Yutaka; Imamura, Tomoaki
ABSTRACT: This study clarified the age of death in patients with or without diabetes using the largest health insurance database in Japan. This population‐based retrospective cohort study was performed using the National Database of Health Insurance Claims and Specific Health Checkups of Japan (NDB) data. The ages of death between people with and without diabetes were compared. A total of 142, 277, 986 patients (74, 488, 962 women and 67, 789, 024 men) over 6 years, including 4, 647, 016 females, and 6, 507, 817 males with diabetes, were included. 2, 786, 071 females and 2, 975, 876 males died over 6 years, including 652, 699 females and 954, 655 males with diabetes. The average age of death in patients with diabetes was 2.6 years less than that of patients without diabetes. This descriptive epidemiological study illustrated the difference in age at death of patients with and without diabetes. Abstract : Our descriptive epidemiological study illustrated the difference in age at death in patients with and without diabetes. Further continuous studies on the ages of death in people with and without diabetes are needed to ensure that the difference is shrinking due to the treatment of diabetes.